Polymicrobial Biofilm Interaction Between Histophilus somni and Pasteurella multocida - Petruzzi, Briana; Dickerman, Allan; Lahmers, Kevin; Scarratt, William K.; Inzana, Thomas J. (Frontiers in Microbiology, 2020)
Histophilus somni and Pasteurella multocida are two of multiple agents responsible for bovine respiratory disease (BRD) in cattle. Following respiratory infection of calves with H. somni, P. multocida may also be isolated from the lower respiratory tract. Because H. somni may form a biofilm during BRD, we sought to determine if P. multocida can co-exist with H. somni in a polymicrobial biofilm in vitro and in vivo. Interactions between the two species in the biofilm were characterized and quantified by fluorescence in situ hybridization (FISH). The biofilm matrix of each species was examined using fluorescently tagged lectins (FTL) specific for the exopolysaccharide (EPS) using confocal laser scanning microscopy. Bacterial interactions were determined by auto-aggregation and biofilm morphology. Pasteurella multocida and H. somni were evenly distributed in the in vitro biofilm, and both species contributed to the polymicrobial biofilm matrix. The average biomass and biofilm thickness, and the total carbohydrate and protein content of the biofilm, were greatest when both species were present. Polymicrobial bacterial suspensions auto-aggregated faster than single species suspensions, suggesting physical interactions between the two species. Almost 300 P. multocida genes were significantly differentially regulated when the bacteria were in a polymicrobial biofilm compared to a mono-species biofilm, as determined by RNA-sequencing. As expected, host genes associated with inflammation and immune response were significantly upregulated at the infection site following H. somni challenge. Encapsulated P. multocida isolates not capable of forming a substantial biofilm enhanced an in vitro polymicrobial biofilm with H. somni, indicating they contributed to the polymicrobial biofilm matrix. Indirect evidence indicated that encapsulated P. multocida also contributed to a polymicrobial biofilm in vivo. Only the EPS of H. somni could be detected by FTL staining of bovine tissues following challenge with H. somni. However, both species were isolated and an immune response to the biofilm matrix of both species was greater than the response to planktonic cells, suggesting encapsulated P. multocida may take advantage of the H. somni biofilm to persist in the host during chronic BRD. These results may have important implications for the management and prevention of BRD.